2022
DOI: 10.1155/2022/1458320
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Combinations of Plasma lncRNAs and mRNAs as Potential Biomarkers for Precursor Lesions and Early Gastric Cancer

Abstract: Patients with gastric cancer (GC) are usually first diagnosed at an advanced stage due to the absence of obvious symptoms at an early GC (EGC) stage. Therefore, it is necessary to identify an effective screening method to detect precursor lesions of GC (PLGC) and EGC to increase the 5-year survival rate of patients. Cell-free RNA, as a biomarker, has shown potential in early diagnosis, personalised treatment, and prognosis of cancer. In this study, six RNAs (CEBPA-AS1, INHBA-AS1, AK001058, UCA1, PPBP, and RGS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Moreover, PPBP has also been identified as a biomarker for other diseases, such as cancers ( e.g . gastric cancer ( Chen et al, 2022 ) and thyroid carcinoma ( Zhang et al, 2021b )), inflammation ( e.g . rheumatoid arthritis ( Guerrero et al, 2021 )), neurosyphilis ( Li et al, 2020 ), COVID-19 ( Yatim et al, 2021 ), and metabolic disease ( e.g .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PPBP has also been identified as a biomarker for other diseases, such as cancers ( e.g . gastric cancer ( Chen et al, 2022 ) and thyroid carcinoma ( Zhang et al, 2021b )), inflammation ( e.g . rheumatoid arthritis ( Guerrero et al, 2021 )), neurosyphilis ( Li et al, 2020 ), COVID-19 ( Yatim et al, 2021 ), and metabolic disease ( e.g .…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that CEBPA-DT was upregulated in cisplatin resistance OSCC cells, CEBPA-DT regulated cisplatin chemosensitivity through CEBPA/BCL2-mediated cell apoptosis [ 40 ]. For gastrointestinal cancer, the prognostic value of CEBPA-DT was illustrated along with several other lncRNAs (INHBA-AS1, AK001058, UCA1, PPBP, and RGS18) in early gastric cancer [ 41 ]. Last but foremost, a recently published paper documented that CEBPA-DT was capable of promoting the EMT process and liver cancer progression [ 32 ], but the mechanism underlying the promoting effect was not illuminated.…”
Section: Discussionmentioning
confidence: 99%
“…This model serves as a more precise diagnostic biomarker than CA19-9 and CEA. Chen et al conducted a study on a combination of four lncRNAs (CEBPA-AS1, INHBA-AS1, AK001058, and UCA1) and two miRNAs (PPBP and RGS18) 177 . They discovered that the combination of three lncRNAs (INHBA-AS1, AK001058, and UCA1) and one miRNA (RGS18) had the best diagnostic performance, with an AUC of 0.820, sensitivity of 0.782, and specificity of 0.708 177 .…”
Section: Biomarker Screening For Early Gastric Cancermentioning
confidence: 99%